Jockeys on Mechanical Donkeys: Modes of Alternative Transportation in an African Metropolis - Huszthyová, Liliana (Lidé města, 2011)
On the example of transportation services this paper discusses the dynamics of present-day globalization processes in Khartoum, Sudan. Building on the dialectical relation between concepts of adaptation and creativity, the article aims to show how individuals display resilience, flexibility and determination to survive by ways of harnessing modernity for their own purposes. Rickshaws as newcomers to the transportation market in Sudan undergo a continuous process of appropriation and adaptation into the Sudanese context. The current article is an attempt to capture some of the notions that control the negotiated (dis)order for such traveling and globalized technologies.